Convenient access to 1, 3,4-trisubstituted pyrazoles carrying 5-nitrothiophene moiety via 1,3-dipolar cycloaddition of sydnones with acetylenic ketones and their antimicrobial evaluation - Rai, N. Satheesha; Kalluraya, Balakrishna; Lingappa, B.; Shenoy, Shaliny; Puranik, Vedavati G. (European Journal of Medicinal Chemistry, 2008)
Novel 1-aryl-3-(5-nitro-2-thienyl)-4-aroyl-pyrazoles 7 have been synthesized by the 1,3-dipolar cycloaddition of 3-arylsydnones 3 with 1-aryl-3-(5-nitro-2-thienyl)-2-propyn- 1-ones 6. The newly synthesized compounds were well characterized by elemental analysis, IR, (1)H NMR and mass spectral studies. They were also screened for their antibacterial and antifungal activities against a variety of microorganisms and the results of such studies have been discussed in this article. (c) 2007 Elsevier Masson SAS. All fights reserved.
Keywords: 1; 3-dipolar cycloaddition; 5-nitrothiophene; acetylenic ketone; Antibacterial; antifungal; Pyrazole; sydnone

Fluconazole analogues containing 2H-1,4-benzothiazin-3(4H)-one or 2H-1,4-benzoxazin-3(4H)-one moieties, a novel class of anti-Candida agents - Borate, Hanumant B.; Maujan, Suleman R.; Sawargave, Sangmeshwer P.; Chandavarkar, Mohan A.; Vaiude, Sharangi R.; Joshi, Vinay A.; Wakharkar, Radhika D.; Iyer, Ramki; Kelkar, Ramesh G.; Chavan, Subhash P.; Kunte, Sunita S. (Bioorganic & Medicinal Chemistry Letters, 2010)
As a part of our program to develop new antifungal agents, a series of fluconazole analogues was designed and synthesized wherein one of the triazole moieties in fluconazole was replaced with 2H-1,4-benzothiazin-3(4H)-one or 2H-1,4-benzoxazin-3(4H)-one moiety. The new chemical entities thus synthesized were screened against various fungi and it was observed that the compounds 4a and 4i are potent inhibitors of Candida strains. The structure-activity relationship for these compounds is discussed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Benzothiazinone; Benzoxazinone; Fluconazole

Synthesis and biological evaluation of new 2-chloro-3-((4-phenyl-1H-1,2,3-triazol-1-yl)methyl)quinoline derivatives via click chemistry approach - Kategaonkar, Amol H.; Shinde, Pravin V.; Kategaonkar, Atul H.; Pasale, Sharad K.; Shingate, Bapurao B.; Shingare, Murlidhar S. (European Journal of Medicinal Chemistry, 2010)
Synthesis of new 2-chloro-3-((4-phenyl-1H-1,2,3-triazol-1-yl)methyl)quinoline derivatives (4a-h) using 1,3-dipolar cycloaddition (click chemistry) reaction of 3-(azidomethyl)-2-chloro-quinoline derivatives (3a-h) with phenyl acetylene in the presence of Cu(I) catalyst has been achieved in very high yield. These molecules were evaluated in vitro for their antifungal and antibacterial activity. Most of the compounds exhibited significant antifungal and antibacterial activity against all the tested strains. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: 1; 2; 2-Chloro3-formyl quinoline; 3-Triazole; Antibacterial; antifungal; Click chemistry

Active pharmaceutical ingredient (api) from an estuarine fungus, microdochium nivale (Fr.) - Bhosale, Siddharth H.; Patil, K. B.; Parameswaran, P. S.; Naik, C. G.; Jagtap, T. G. (Journal of Environmental Biology, 2011)
Various marine habitats sustain variety of bio-sources of ecological and biotech potentials. Pharmaceutical potential compound Cyclosporine A was reported from marine fungus Microdochium nivale associated with Porteresia coarctata, a marine salt marsh grass from mangrove environment distributed along the Central West Coast (CWC) of India. This study involves association of M. nivale with P. coarctata plant, fermentation conditions, purification of Cyclosporine A, chemical characterization etc. Its antifungal inhibition and MIC (Minimum inhibitory concentration) against Aspergillus strains (A. niger, A. japonicus, A. fresenii), yeasts and dermatophytes (Candida sp., Cryptococcus neoformans, Trichophyton mentagrophytes, T tonsurans, T violaceum, Microsporium gypsum and Fusarium sp.) were evaluated. However, the MIC against A. japonicus, C. neoformans, Candida sp. and T. tonsurans were confirmed to be as low as 12.5-25 mg disc(-1). The antifungal properties of Cyclosporine A against Aspergillus species, yeast and dermatophytes revealed that Cyclosporine A would be a potential compound for life threatening diseases caused by above fungi in both human and animals. Furthermore, we have reported herewith another source of Cyclosporin A derived from filamentous fungus, M. nivale. occurring in marine environment.
Keywords: antifungal; Cyclosporine A; Estuarine environment; Microdochium nivale

Antifungal activity and mechanism of action of carvacrol and thymol against vineyard and wine spoilage yeasts - Chavan, Pradnya S.; Tupe, Santosh G. (Food Control, 2014)
Antimicrobial activity of carvacrol and thymol against natural yeast flora of the grapes and yeasts known to cause wine spoilage was examined. Carvacrol and thymol exhibited comparable or better antifungal activity than potassium metabisulphite, commercially used wine preservative, against the natural yeast flora and spoilage yeasts. The antifungal activity for both the compounds was better at pH 3.5 than pH 6.5. Addition of carvacrol and thymol (64 mu g/mL) in red wine resulted in inhibition of growth of the spoilage yeasts. Carvacrol and thymol exerted their antimicrobial action through membrane damage, leakage of cytoplasmic content and ergosterol depletion. In conclusion, carvacrol and thymol holds promise as a potential natural preservative for the control of wine spoilage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Carvacrol; Thymol; Wine spoilage

Antifungal dimeric chalcone derivative kamalachalcone E from Mallotus philippinensis - Kulkarni, Roshan R.; Tupe, Santosh G.; Gample, Suvarna P.; Chandgude, Macchindra G.; Sarkar, Dhiman; Deshpande, Mukund V.; Joshi, Swati P. (Natural Product Research, 2014)
From the red coloured extract (Kamala) prepared through acetone extraction of the fresh whole uncrushed fruits of Mallotus philippinensis, one new dimeric chalcone (1) along with three known compounds 1-(5,7-dihydroxy-2,2,6-trimethyl-2H-1-benzopyran-8-yl)-3-phenyl-2-propen -1-one (2), rottlerin (3) and 4 `-hydroxyrottlerin (4) were isolated. The structure of compound 1 was elucidated by 1D and 2D NMR analyses that included HSQC, HMBC, COSY and ROESY experiments along with the literature comparison. Compounds 1-4 were evaluated for antifungal activity against different human pathogenic yeasts and filamentous fungi. The antiproliferative activity of the compounds was evaluated against Thp-1 cell lines. Compounds 1 and 2 both exhibited IC50 of 8, 4 and 16 mu g/mL against Cryptococcus neoformans PRL518, C. neoformans ATCC32045 and Aspergillus fumigatus, respectively. Compound 4, at 100 mu g/mL, showed 54% growth inhibition of Thp-1 cell lines.
Keywords: 4 `-hydroxyrottlerin; antifungal; dimeric chalcone; kamalachalcone E; Mallotus philippinensis; rottlerin

Synthesis and antifungal potential of 1,2,3-triazole and 1,2,4-triazole thiol substituted strobilurin derivatives - Chaudhary, Preeti M.; Tupe, Santosh G.; Jorwekar, Shweta U.; Sant, Duhita G.; Deshpande, Sunita R.; Maybhate, Shailaja P.; Likhite, Anjali P.; Deshpande, Mukund V. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2015)
beta-Methoxyacrylate group is an important pharmacophore of commercially used strobilurin fungicides. In the present study, a total of seventeen 1,2,4-triazole thiols 8a-h and 1,2,3-triazole substituted 10a-i strobilurin derivatives have been synthesized. 1,2,4-Triazole thiol substituted strobilurin derivatives 8a-h have been found to inhibit the growth of plant pathogens such as Fusarium oxysporum, Magnaporthe grisea, Drechslera oryzae and human pathogens Aspergillus fumigatus and different strains of Cryptococcus neoformans, with MIC in the range of 16-256 mu g/mL. In case of Candida albicans tested strain, the MIC is > 256 mu g/mL. p-Chlorophenyl substituted 1,2,4-triazole thiol strobiulrin derivative 8e is the most potent inhibitor with MIC of 16-64 mu g/mL against most of the tested pathogens. Antifungal action of the compounds is due to inhibition of mitochondrial respiration. In the resazurin reduction assay, EC50 for inhibition of RZ reduction in D. oryzae by azoxystrobin and 8e are 3.42 +/- 0.03 mu g/mL and 3.63 +/- 0.21 mu g/mL, respectively; while in case of C. neoformans, EC50,, of azoxystrobin and 8e are between 0.65-0.85 mu g/mL. In a non-pathogenic model Benjaminiella poitrasii, though the MIC for all the synthesized compounds 8a-h and 10a-i are > 256 mu g/ml, yeast to hypha transition is inhibited in the range of 21-75% at 4 mu g/mL concentration while EC50 for inhibition of RZ reduction by azoxystrobin and 8e are 31.5 +/- 0.4 mu g/mL and 17.95 +/- 0.7 mu g/mL, respectively. The 50% germ tube formation inhibition in case of C. albicans is observed at 108.49 mu g/mL. 1,2,4-Triazole thiol substituted strobilurin derivatives hold promise for the control of pathogenic fungi in agriculture and health care.
Keywords: 1; 2; 3-triazole strobilurin; 4-triazole thiol strobilurin; antifungal; Strobilurin; Y-H transition inhibition

Novel tetrazoloquinoline-rhodanine conjugates: highly efficient synthesis and biological evaluation - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman; Yeware, Amar; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and Mycobacterium bovis BCG, a small focused library of rhodanine incorporated tetrazoloquinoline has been efficiently synthesized by using [HDBU][HSO4] acidic ionic liquid. The compound 3c found to be promising inhibitor of MTB H37Ra and M. bovis BCG characterized by lower MIC values 4.5 and 2.0 mu g/mL, respectively. The active compounds were further tested for cytotoxicity against HeLa, THP-1, A549 and PANC-1 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Again, the synthesized compounds were found to have potential antifungal activity. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target Zmp1 enzyme of MTB H37Ra, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of in vitro and in silico study suggest that these compounds possess ideal structural requirement for the further development of novel therapeutic agents. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Antitubercular; Cytotoxicity; Docking study; Rhodanine derivatives

Regioselective synthesis of 1,4,5-trisubstituted 1,2,3-triazole derivatives from alpha,beta-unsaturated carbonyls - Verma, Naimish K.; Bera, Smritilekha; Gonnade, Rajesh; Mondal, Dhananjoy (European Journal of Organic Chemistry, 2022)
The copper-catalyzed oxidative azide-olefin cycloaddition (OAOC) reaction of differently substituted alpha,beta-unsaturated carbonyls with azides provided an efficient method for preparing biologically active 1,4,5-trisubstituted 1,2,3-triazoles. In this study, the cycloaddition reaction was found to be a simple and powerful method for constructing diverse mono- and bis-(1,4,5-trisubstituted 1,2,3-triazole) functionalized heterocyclic compounds in moderate to high yields with great regioselectivity. The XRD-analysis data of one of the bis-triazole derivatives supported the regioselectivity as well as the conformity of the method in the construction of the triazole nucleus. The preliminary antifungal profile against C. albicans was observed with cinnamaldehyde-based triazole derivatives demonstrating promising results.
Keywords: alpha; antifungal; beta-Unsaturated carbonyls; Cycloaddition; Dibenzalacetone; Triazole

Sustainable fabrication of copper nanoparticles: a potent and affordable candidate for water treatment, water disinfection, antioxidant activity and theranostic agent - Sinha, Tanur; Adhikari, Partha Pradip; Bhandari, Vinay M. (ChemistrySelect, 2022)
This study reports a simple, green, and large-scale biosynthetic fabrication of spherical copper nanoparticles (Cu NPs), approximate 28 nm, using the aqueous extracts of Diaplazium esulentum (Retz.) Sw. fern. Characterization was carried out for morphology, size, elemental analysis, crystallinity and for identification of functionalities responsible for reduction and stabilization. Extraordinary remediation efficiency was obtained for the developed Cu NPs for the elimination of two industrially important pollutants; Methyl Violet 6B and Methylene Blue (greater than 92 % within 150 mins). A mechanism was postulated for the process using the data on the identification of NPs and also spent NPs apart from degraded products. Furthermore, the Cu NPs revealed excellent antibacterial activity against gram positive bacteria: Staphylococcus aureus, Streptococcus pneumonia and Bacillus subtilis, as well as gram negative bacteria: Pseudomonas aeruginosa, Escherichia coli and potential action against fungal strains; Aspergillus niger and Candida albicans. Additionally, the assay depicted that Cu NPs has fairly decent radical scavenging activity with IC50 value 2.11 mM. Moreover, the Cu NPs were found to exhibit profound anticancerous activity against two human cancer line cells. The present research work has implications for exploitation of DE fern extract for the development of Cu NPs and their numerous applications ranging from pollutants removal to antibacterial, antifungal, antioxidant and anticancerous agents.
Keywords: Anticancer; antifungal; Antimicrobial; Antioxidant; Photodegradation and Phytosynthesis

An integrated paradigm to understand the antibacterial and antifungal potential of bimetallic core-shell platinum silver (Pt@Ag) nanoparticles: A one health approach - Bamb, Aagam Lalit; Varma, Sanjana; Gade, Tejas Subhash; Palaskar, Shahaji; Vamkudoth, Koteswara Rao; Vyawahare, Niraj; Chaudhari, Pallavi M.; Chaudhari, Bhushan P. (Microbial Pathogenesis, 2025)
The concurrent occurrence of various microbial infections escalates the need to develop new treatments that can tackle multiple microbes and improve clinical outcomes. This study reports the synthesis and comprehensive evaluation of core-shell platinum-silver nanoparticles (Pt@AgNPs) designed to elucidate the antimicrobial effects while ensuring biocompatibility. The synthesis protocol was meticulously optimized to investigate the impact of precursor concentrations and reagent conditions. High-end characterization confirmed the formation of a welldefined core-shell structure with spherical morphology, crystalline nature, a face-centred cubic (FCC) lattice, high monodispersity, and stability, with a mean size of 20.344 +/- 4.492 nm. The antimicrobial potential of Pt@AgNPs was validated through a minimum inhibitory concentration (MIC) assay, revealing potent activity with MIC values of 15.6 mu g/mL for Pseudomonas aeruginosa and Staphylococcus aureus and 3.9 mu g/mL for Escherichia coli. Antibiofilm assay demonstrated significant inhibition of biofilm formation by P. aeruginosa at concentrations as low as 3.9 mu g/ml. The nanoparticles also exhibited notable antifungal activity, as indicated by an inhibition of 65.19 % for Aspergillus niger and 61.82 % for Fusarium verticillioides. Furthermore, hemocompatibility was noticed with the hemolysis assay, and the antioxidant properties of nanoparticles, assessed through the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, underscored their potential to mitigate oxidative stress. This integrative study positions Pt@AgNPs as a promising platform for combating the occurrence of co-infections. The core-shell nanoparticle serves as a versatile tool in antimicrobial defence, exhibiting antibacterial, antifungal, antibiofilm, and antioxidant activity. Thus, it highlights their commercial translational potential as a next-generation antimicrobial intervention.
Keywords: Antibacterial; antibiofilm; antifungal; Antioxidant; Co-infections; Pt@Ag nanoparticles